Privileged yet vulnerable: Shared memories of a deeply gendered lockdown. (16th April 2021) - Ryan, Irene; Hurd, Fiona; Mudgway, Cassandra; Myers, Barbara
Abstract: The centrality of personal experience plays a pivotal role in feminist scholarship. We draw on the feminist inspired collaborative inquiry research method, memory‐work, to bring to the fore our experiences of living and working in lockdown, a Government enforced policy response to the global Covid‐19 pandemic in Aotearoa New Zealand. Memory‐work provided the conduit for us to work collaboratively with our experiences and make sense of the whirlwind we lived through. Our exploration is set against the backdrop of the challenges of the conservatism endemic in the neoliberal pathway taken in NZ and its transmission into the university sector. Through our collective editing of each account generated by the phrase "her murky boundaries of lockdown" two interconnected themes came to the fore in various guises: restricted and vulnerable. Using á collective "she" and "her, " we reconstruct and analyze the nuances of our shared experiences revealing layers of gendered vulnerability paradoxically intertwined with privilege at this unprecedented time. We conclude by arguing that lockdown exacerbated already existing divisions reinforcing how female, feminist, and academic remain an uncomfortable fit.